Plant growth analysis of wheat populations in a long-term field-experiment - Vári, Enikő; Pepó, Péter (Acta Agraria Debreceniensis, 2012)
The experiments were conducted as part of the long-term trial adjusted, in triculture (pea-wheat-corn) and biculture (wheat-corn), at three nutrition levels, with the use of one crop protection technologie (conventional) at the Látókép Research Site of the Centre of Agricultural Scienses, University of Debrecen, on a chernozem soil. The wheat variety used in the long-term trial was GK Csillag, which was sown at 5,8 million germs/ha. The effect of pre-crops and nutrient-supply levels on some growth-parameters (LAI, HI, LAD), just as SPAD-values and yield amounts of winter wheat has been investigated in this experiment. We tried to find out the extent of relationship between the different parameters, so we determined the relationships between different nutrient-supply levels, yield amounts, LAI- SPAD- and LAD-values – measured in the crop-year of 2010–2011 in different crop rotation systems – by using correlation analysis. It has been stated both in case of bi- and tri-culture crop-rotation systems that different fertilizer dosages had significantly affected the leaf area index dynamics and its maximal value, and that increasing N+PK fertilization has significantly increased the duration of leaves, as well. The highest SPAD-values were measured during the flowering and grain filling stages. However, we haven’t revealed significant differences between all fertilizer treatments. In case of the bi-culture crop-rotation system harvest index values showed an increasing tendency parallel to the increasing nutrient-supply levels, while in case of the tri-culture system this tendency was rather decreasing. However, these differences were not significant. Parallel to the increasing fertilizer dosages yield results were increased in a significant extent. At the same nutrient supply-levels 2088–4615 kg ha-1 higher yields were measured in the tri-culture than in the bi-culture system. The correlation analyses have confirmed that all of the investigated parameters (yield amount, LAI, SPAD, LAD) had almost in all cases close positive correlation to the nutrient-supply level and the yield amount in both crop-rotation systems. These results have confirmed that the leaf area, the leaf duration, the SPAD-values and the fertilization have altogether resulted in the production of maximum grain yields.